Transformation Caused by Marine Sediment Mining in Karimun Besar Island: A Documentary Analysis and Its Implications for Non-Traditional Maritime Security - Agustin, Mayang; Laksdya TNI (Purn) Dr. Widodo, S.E., M.Sc.; Laksma TNI (Purn.) Dr. Ir. Trismadi, M.Si., IPU (International Journal of Education, Vocational and Social Science, 2025)
Marine sediment mining in the Riau Islands Province, particularly around Karimun Besar Island, has created a multidimensional challenge involving ecological degradation, socio-economic disparities, and maritime security concerns. This study aims to analyze the ecological transformation and its implications for non-traditional maritime security using a qualitative documentary analysis approach. Data were obtained from six scientific journals and institutional reports from BMKG, KLHK, and IOJI. The results reveal that intensive sand extraction has caused significant geomorphological changes, including seabed deformation, shoreline erosion, and mangrove degradation of up to 40% between 2015 and 2023. Although mining activities have increased local household income by approximately 20%, labor absorption remains minimal at only 4%, leading to social inequality and community tension. Furthermore, environmental damage has weakened coastal resilience and triggered non-traditional security threats such as cross-border fishing, smuggling, and local conflicts. The study concludes that marine sediment mining in Karimun Besar represents a paradox of development economic gains coexist with ecological and security degradation. To address this issue, Indonesia must adopt an eco-maritime security governance model that integrates environmental protection, socio-economic sustainability, and inter-agency maritime coordination to maintain national resilience and Good Order at Sea